Tuberculosis diagnostic methods in buffaloes - Oliveira, Gabriela Capriogli [UNESP]; Roxo, Eliana; Burger, Karina Paes [UNESP]; Carvalho, Adolorata Aparecida Bianco [UNESP] (Universidade Estadual de Londrina, 2015)
The low productivity ofbuffalo herds and condemnation of carcasses in slaughterhouses due to tuberculosis lesions have resulted in increasing economic losses because these animals cannot be treated and must be destroyed by sanitary slaughter. Tuberculosis is a widely distributed zoonosis that affects the beef supply chain of the Brazilian agribusiness economically and socially. Like cattle, buffaloes are sensitive to Mycobacterium bovis, which is the main causative agent of zoonotic tuberculosis. Tuberculosis in buffaloes has been reported in several countries, including Brazil. In order to control and eradicate this disease among cattle and buffaloes in Brazil, the Ministry of Agriculture, Livestock, and Supply created the National Program for the Control and Eradication of Brucellosis and Tuberculosis with the main objective of finding a significant number of disease-free herds throughout the national territory using reliable methods. This review summarizes the main data on the history of occurrence of M. bovis in Brazilian herds and the diagnostic methods for the disease in buffaloes. Little information is available on buffalo tuberculosis. Due to the increasing population of buffaloes and their economic importance, more studies investigating the occurrence and identification of tuberculosis in this species are clearly needed.
Keywords: Bovine; Isolation; Mycobacterium bovis; Zoonosis